(untitled) (Journal of the College of Basic Education, 2023)
This study aims to clarify the role of the necessary purposes in the purified Sunnah of the Prophet through the book (Sunan An-Nasa’i) - The Purpose of Preserving Religion as a model - . His death, and he mentioned the hadiths that the wise legislator put in place, to preserve the purpose of preserving the religion, this memorization included two aspects: the aspect of existence, or the so-called positive rulings, and the aspect of non-existence, or the so-called negative rulings, then I mentioned the ruling of the hadith, and then I explained the hadith as it came in He wrote the explanations of the hadiths, and then showed the purpose of the hadith, then the conclusion of the research .